48‐1: Solid‐State Laser Crystallization for Poly‐Si TFTs and Their Applications. Issue 1 (28th June 2022) - Tanabe, Hiroshi; Obata, Hideki; Hayashi, Ken-ichi; Hamada, Keita; Shoji, Isao; Mori, Shigeru
Abstract : We demonstrate for the first time that a pulsed solid‐state laser with a wavelength of 343 nm has the potential to fabricate poly‐Si films equivalent to the conventional ones and that they can be applied to TFTs and OLED displays for practical use. This suggests that this laser could replace the excimer laser used in the crystallization process for LTPS technology and also that it might contribute to reducing the cost of ownership in industry.